2017
DOI: 10.1016/j.jcmg.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Trials of Quality Improvement in Imaging

Abstract: Cardiovascular imaging plays a central role in the diagnosis and treatment of cardiovascular disease. Recently, increased emphasis has been placed on quality in cardiovascular imaging, and it is becoming a central priority for various stakeholders, including patients, physicians, and payers. The changing health care landscape and associated challenges imposed on cardiac imagers, including reductions in reimbursement and growing need for pre-authorization, have also helped bring quality metrics to the forefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Reports on quality improvement in CV imaging have thus far focused primarily on appropriate use criteria, image acquisition and reporting, and educational interventions. 7 To our knowledge, this study is the first to report the impact of a standardized secondary review process in decreasing DE on TTE in patients undergoing CHD surgery. In this study, we have shown that by instituting a systematic second review of preoperative imaging for patients undergoing CHD surgery, we were able to decrease the frequency of DE, especially moderate and major DE, and we were able to prevent one third of DEs from reaching the patient.…”
mentioning
confidence: 88%
“…Reports on quality improvement in CV imaging have thus far focused primarily on appropriate use criteria, image acquisition and reporting, and educational interventions. 7 To our knowledge, this study is the first to report the impact of a standardized secondary review process in decreasing DE on TTE in patients undergoing CHD surgery. In this study, we have shown that by instituting a systematic second review of preoperative imaging for patients undergoing CHD surgery, we were able to decrease the frequency of DE, especially moderate and major DE, and we were able to prevent one third of DEs from reaching the patient.…”
mentioning
confidence: 88%
“…The final intervention component, the AA, was selected because our institution has frequently employed point-of-care CDS in other clinical settings and because CDS will soon be required for all advanced imaging procedures by the Centers for Medicare & Medicaid Services. [6][7][8]22,25 The AA was triggered when a clinician queued up a stress echo order in the EHR for a patient who did not have a contraindication for stress ECG based on their problem list (i.e., list of diagnoses before encounter; Figure 2). It displayed a noninteractive decision tree to guide the selection of an appropriate stress test and included links to applicable references.…”
Section: Alternative Alertmentioning
confidence: 99%
“…6,[15][16][17][18][19][20][21] Findings suggest that isolated education initiatives are of limited value, but point-of-care CDS, including decision trees, mobile applications, and interactive ordering prompts, have been associated with improvements in the appropriateness of ordered tests. [6][7][8]22 Overall, multi-faceted approaches have been shown to be most successful in generating practice change, but few studies have targeted echocardiograms and most focus on single specialties. 7,8,[18][19][20][21][22][23] One notable exception is the Echo WISELY randomised controlled trial which showed that a multicomponent initiative targeting primary care providers (PCPs) and cardiologists decreased the number rarely appropriate transthoracic echocardiogram orders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Quality improvement in echocardiography is a burgeoning field with reports of system and patient-level improvements after implementing this methodology. [5][6][7] To attain consistent quality imaging, the American Society of Echocardiography recommends performing several routine measurements in screening echocardiograms and follow-up echocardiograms for structural heart disease. 8 Also, lesion-specific protocols are recommended to aid in serial assessments.…”
Section: Introductionmentioning
confidence: 99%